Typhoid conjugate vaccines for preventing typhoid fever (enteric fever) - Gloeck, Natasha R; Leong, Trudy D; Mthethwa, Mashudu; Iwu-Jaja, Chinwe Juliana; Katoto, Patrick Dmc; Wiysonge, Charles S; Kredo, Tamara (Cochrane database of systematic reviews, 2025)
Typhoid fever is a major cause of enteric disease-related morbidity and mortality. Vaccination reduces disease burden and prevents outbreaks, but policies and programmes should be informed by the most recent evidence as newer vaccines become available. To assess the benefits and harms of typhoid conjugate vaccines (TCVs) compared to no vaccine, placebo, typhoid-inactive agents (vaccines for another disease) or other typhoid vaccines for preventing morbidity and mortality associated with typhoid fever in adults and children. In April 2024, we searched the Cochrane Central Register of Controlled Trials, MEDLINE, Embase, CINAHL, Global Index Medicus, United States Advisory Committee on Immunization Practices and the World Health Organization vaccine repository for randomised controlled trials (RCTs), with no restrictions. We also searched clinical trial registries for ongoing trials (www. gov and the WHO International Clinical Trials Registry Platform), grey literature, bibliographic citations of reviews and key articles for additional studies. We contacted study authors for information about ongoing studies. We included RCTs and cluster-RCTs of children and adults living in typhoid-endemic areas or travelling to typhoid-endemic areas. We included studies comparing TCVs to controls (i.e. no vaccine, placebo or vaccines for another disease), non-conjugated typhoid vaccines or other TCVs. Outcomes included acute typhoid fever, defined by laboratory-confirmed isolation of Salmonella typhi, all-cause mortality, adverse events (AEs) and serious adverse events (SAEs). Review authors independently assessed risk of bias for all outcomes, using the Cochrane RoB 2 tools. We resolved disagreements through discussion or adjudication. We assessed the intention-to-treat effect and used the overall RoB judgement to assess the certainty of evidence for each outcome. Three review authors independently screened titles and abstracts for eligible studies, followed by full-text assessment. Disagreements were resolved through discussion or adjudication by a fourth author. Four authors independently extracted characteristics of included studies and outcome data using a piloted, standardised data extraction form. We synthesised results for each outcome where possible, using the Mantel-Haenszel statistical method and random-effects analysis model. Where meta-analysis was not possible due to the nature of the data, we planned to synthesise results based on direction of effect. We used GRADE to assess the certainty of evidence for each outcome, assessing risk of bias, inconsistency, indirectness, imprecision and other bias. We included 19 trials (17 RCTs and two cluster-RCTs). The 19 trials enrolled 395,650 participants, with ages ranging from six weeks to 60 years. Vaccines were delivered as a single dose in 14 studies; two doses, ranging from four to 24 weeks apart, in six studies; and three doses, four weeks apart, in one study. Comparators included: no vaccine, placebo and other vaccines. Seven studies compared TCV with non-conjugated typhoid vaccines. Six studies compared one TCV to another TCV. TCV compared to control may result in a large reduction in acute typhoid fever (risk ratio (RR) 0.20, 95% confidence interval (CI) 0.12 to 0.32; I = 70%; 6 studies, 101,896 participants; low-certainty evidence) and probably results in little to no difference in all-cause mortality (RR 0.80, 95% CI 0.35 to 1.85; I = 52%; 4 studies, 100,337 participants; moderate-certainty evidence). TCV results in little to no difference in AEs when compared to control (RR 0.91, 95% CI 0.76 to 1.09; I = 0%; 3 studies, 29,465 participants; high-certainty evidence) and a slight reduction in SAEs compared to control (RR 0.82, 95% CI 0.71 to 0.95; I = 0%; 6 studies, 89,625 participants; high-certainty evidence). TCV compared to non-conjugated typhoid vaccines may result in little to no difference in acute typhoid fever (RR 0.90, 95% CI 0.48 to 1.69; 1 study, 78 participants; low-certainty evidence). There were no deaths in the included studies. When compared to non-conjugated typhoid vaccines, TCV likely results in little to no difference in AEs (RR 1.00, 95% CI 0.77 to 1.31; I = 0%; 3 studies, 244 participants; moderate-certainty evidence) and likely results in a slight reduction in SAEs (RR 0.30, 95% CI 0.05 to 1.88; I = 0%; 2 studies, 732 participants; moderate-certainty evidence). For TCV compared to another TCV, none of the studies reported on acute typhoid fever. Vi tetanus toxoid vaccine (Vi-TT) may result in little to no difference in all-cause mortality compared to a different TCV (RR 5.19, 95% CI 0.54 to 49.80; I = 0%; 2 studies, 2422 participants; low-certainty evidence). Vi-TT likely results in little to no difference in AEs compared to another TCV (RR 1.18, 95% CI 0.92 to 1.51; I = 39%; 4 studies, 2916 participants; moderate-certainty evidence) and may result in little to no difference in SAEs (RR 2.48, 95% CI 0.74 to 8.36; I = 0%; 3 studies, 2866 participants; low-certainty evidence). The certainty of evidence was consistently reduced due to imprecision, indirectness and bias. This review highlights that TCVs, compared to controls, are effective in preventing typhoid fever, and may confer protection for up to four years. TCVs compared to non-conjugated typhoid vaccines may result in little to no difference in acute typhoid fever and AEs, and likely result in a slight reduction in SAEs. Vi-TT compared to another TCV may result in little to no difference in all-cause mortality or SAEs, and likely results in little to no difference in AEs. NG, TL and TK were partly supported by, and the Cochrane Infectious Diseases Group (CIDG) editorial base is funded by, the Research, Evidence and Development Initiative (READ-It), funded by UK aid for the benefit of low- and middle-income countries (project number 300342-104). The views expressed in this review do not necessarily reflect the official policies of the UK government. Protocol available via doi.org/10.1002/14651858.CD015746.